2016
DOI: 10.1016/j.psychres.2016.06.057
|View full text |Cite
|
Sign up to set email alerts
|

Maternal T. gondii, offspring bipolar disorder and neurocognition

Abstract: Prenatal exposure to maternal Toxoplasma gondii (T. gondii) IgG antibody titer has been associated previously with an increased risk of offspring schizophrenia (SZ) and cognitive impairment. We examined maternal T. gondii, offspring bipolar disorder (BP) and childhood cognition using a population-based birth cohort. Maternal sera, drawn in the third trimester, were analyzed for T. gondii IgG antibody titer, and offspring cognition at ages 5 and 9–11 was measured with the Peabody Picture Vocabulary Test (PPVT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Studies in several countries have found a higher seroprevalence of T. gondii infection in patients suffering from bipolar disorder than in controls (17–22). In contrast, no association between maternal infection with T. gondii and risk of bipolar disorder in offspring was found (23, 24). Bipolar disorder is a public health problem around the worldwide, and about 1% of the population suffers from this disease (25, 26).…”
Section: Introductionmentioning
confidence: 94%
“…Studies in several countries have found a higher seroprevalence of T. gondii infection in patients suffering from bipolar disorder than in controls (17–22). In contrast, no association between maternal infection with T. gondii and risk of bipolar disorder in offspring was found (23, 24). Bipolar disorder is a public health problem around the worldwide, and about 1% of the population suffers from this disease (25, 26).…”
Section: Introductionmentioning
confidence: 94%
“…Several studies showed that increased levels of maternal antibodies to T. gondii are associated with a higher risk of schizophrenia spectrum disorders in adult offspring [65,67]. Contrary to this, no significant association was found between prenatal exposure to T. gondii and the risk of BD in adult offspring, suggesting that congenital T. gondii infection could be a risk factor only for the development of schizophrenia and related psychosis, but not for BD [65,68,69]. Only one study, investigating whether certain Toxoplasma genotypes may be differentially associated with the risk of psychosis, found that the offspring of mothers with a serological pattern consistent with Toxoplasma genotype I infection were at significantly increased risk for the development of psychosis as compared with the matched unaffected control mothers, and the risk was statistically significant only for affective psychosis, including schizoaffective disorder-bipolar type, BD with psychotic features and major depressive disorder with psychosis.…”
Section: Relationship Between Toxoplasma Gondii and Bipolar Disordermentioning
confidence: 99%
“…When more than one study existed from the same team with overlapping patients for the same type of SCZ outcome (SCZ or SCZ phenotype), we kept only the publication with the largest number of patients with SCZ. Studies exploring the association between maternal Toxoplasma seropositivity and SCZ in the offspring ( 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ) were not included in our analysis. Positive Toxoplasma IgG antibodies in the newborn infant's Guthrie card blood sample reflect the maternal T. gondii infection status from transplacentally transferred maternal Toxoplasma IgG antibodies to the fetus, and additional neonatal testing is required to confirm whether the newborn infant is congenitally infected or not.…”
Section: Methodsmentioning
confidence: 99%